Penyusunan Model Konsepsual Basisdata untukSistemlnformasiKadasterMultiguna - Rochmad Muryamto (Forum Teknik, 2003)
The term  of nrultipurpose cadastre is  used to  describe a system  that  is  designed  to  record'store, and  provide  not  only landlenure and land  valuation  idormation  but also a wide varietyof information that  ,o,  u,u f*rtionally related  to  and  referenced  by  property  parcels'  It  meansthat  multipurpose no,t  oniy ,eceiues  information and data from many sources' but it  alsoprovides  services and  products for many purposes and  users'  The  research  is  directed  to  designa  conceptual model  oi mltipuipose  cadastre database  for developing  its  information system'The  conceptual model  was  developed using  entity  relationship diagram  and  represented  inrelational  database  structure. A model  of  multipurpose cadastre,was also  developed  using someparcel  based  data that  came fronr many ,)ur)rr.  The model  was situated  in  KelurahonTahunan,  Yogtakarta'An information system  of multipurpose  cadastre  based  on the conceptual design  can bedeveloped and  it  provided  nol onlyiudicial  andfiscal  information' but  also  semices  informationsuch  as  water,  telephone, and  electricity. In  addition,  some problems  occurred  in  building  themodel were also  discussed'Keywords:  multipurpose  cadastre'  conceptual design